Implementation of Sustainable Food Agricultural Land Protection Policy in South Tondano District, Minahasa Regency - Mandagi, Marthinus; Inof Riisyie Rantung, Margareth; Melisa Onibala, Nancy (Iapa Proceedings Conference, 2023)
This study aims to describe the implementation of sustainable food agriculture land protection policies in the South Tondano district, Minahasa Regency. This study uses a qualitative approach, with data collection techniques through observation, interviews, and documentation. The results showed that: 1) Socialization that was not optimal caused the community to not know the Policy for the Protection of Sustainable Food Agricultural Land. 2) Economic needs and population growth increase the need for residential land which causes people to build buildings in the LP2B referral area. 3) The Village Government does not act decisively and supports the expansion of settlements in Tataaran Village. 4) Violation of land conversion for sustainable food agriculture is the community's non-compliance with regulations as a result of lack of knowledge of policies. So the researchers suggest: 1) It is better for the government to carry out a thorough socialization to the community, not limited to the Village apparatus. 2) It is better for the government to provide solutions for people who do not have alternative options to build houses and places of business, as well as develop a more modern agricultural system so that young people are interested in working in agriculture. 3) It is better for the government as the implementer to have integrity in implementing a policy. 4) It is better for the government to provide regulations with heavier sanctions, for example in the form of fines for violating this regulation.